2018
DOI: 10.1063/1.5051730
|View full text |Cite
|
Sign up to set email alerts
|

Mg and N co-doped CuCrO2: A record breaking p-type TCO

Abstract: We prepare CuCrO2 thin films with magnesium and nitrogen dopants. The solid state reaction method is employed to produce CuCrO2 targets with three different concentrations of Mg (0%, 2.5%, and 5%). The targets are used in an RF sputtering system to prepare thin films in the presence of N2 as the reactive gas. In this manner, Mg and N atoms, respectively, replace Cr and O sites in the CuCrO2 structure and enhance the electrical and optical properties of the host material. This cationic-anionic substitution yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Mg-doped CuCr 1-x Mg x O 2 ) has resulted in p-type layers with conductivities of up to ~200  -1 cm -1 . Analogously, the Mg and N substitution of Cr and O sites (in CuCrO 2 ) resulted in an increased conductivity of up to ∼278  -1 cm −1 [204] , which arguably is the largest conductivity for p-type Cu-based delaffosite oxides reported to date.…”
Section: P-typementioning
confidence: 92%
“…Mg-doped CuCr 1-x Mg x O 2 ) has resulted in p-type layers with conductivities of up to ~200  -1 cm -1 . Analogously, the Mg and N substitution of Cr and O sites (in CuCrO 2 ) resulted in an increased conductivity of up to ∼278  -1 cm −1 [204] , which arguably is the largest conductivity for p-type Cu-based delaffosite oxides reported to date.…”
Section: P-typementioning
confidence: 92%
“…where (Cr Cr ) × represents the Cr in the original lattice sites, (Mg Cr )' represents the Mg 2+ in Cr 3+ site and h + is the positive hole. To date, the highest p-type conductivity of about 278 S•cm −1 has been obtained in Mg and N co-doped CuCrO 2 film deposited by radiofrequency (RF) sputtering, where the Cu vacancies (V Cu ) as well as the substitution of Cr by Mg (Mg Cr ) and O by N (N O ) are considered as the intrinsic acceptor and extrinsic acceptor, respectively [23]. All of them contribute to the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the p-type conductivity increased by more than three orders to 17 S•cm −1 compared to the intrinsic state [123]. By combining both cation and anion substitution, a new record for p-type conductivity in delafossites has been reported to be 278 S•cm −1 in 2018 [124]. In this study, Mg and N dopants were introduced into the CuCrO2 thin film, which served to substitute Cr and O, respectively.…”
Section: Delafossitesmentioning
confidence: 91%
“…Possibly because this paper was published just recently, no other reports on such a high conductivity for this system can be found. Besides the Mg-N doping, other co-doping strategies have also been studied, including Mg-Fe [133], Mg-S [137], and Ag-Mg [138], but the electrical and optical properties are not comparable to the study on Mg-N doping [124].…”
Section: Delafossitesmentioning
confidence: 99%